ASSESSMENT OF THE SUCCESS OF MICRO GRAFTING CLEMENTINE TIMING ON SOUR ORANGE - Salman, Omar N.; Al-Hayany, A.M. Abd; Ibrahim, Kadhim M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was carried out at three locations (Laboratory of Plant Tissue Culture, Fields of the College of Agriculture, University of Diyala and one of the private nursery at the city of Baqubah.  The applied experiments included two separate experiments on the scion Mandarin Clementine micro grafted on Sour orange rootstock. The first micro grafting experiment aimed to develop a method of vegetative propagation of Clementine and transferring the micro grafts  from a laboratory to the field and comparing grafting dates (spring, early autumn, late autumn) with the laboratory grafting after treating grafting region with different concentrations of gibberellin (0, 0.3 or 0.4 mg. L-1). The effect of grafting dates on the percentages of success of grafted plants after one month of acclimatization. The experiment was carried out according to completely randomized design (CRD) as a factorial experiment with two factors and three replications for the first one, and as a single factor experiment with three replicates for the second experiment. Results showed a decline in the percentage of success of the grafting and a slight success correlated with increased gibberellin concentration in the aforementioned experiment at early fall grafting. A second field experiment, was conducted with the aim of studying the success of maintained micro propagated plants during summer season and the effect of foliar spray with salicylic acid (0, 200 or 400 mg. L-1) and marine algae extract (0, 5 or 10 g. L-1) on some characteristics of vegetative growth and some chemical characteristics. The experiment was carried out according to the Randomized Complete Block Design (RCBD), as a factorial experiment with two factors and three replications. No significant effect for both factors was recorded in most vegetative characteristics, while chemical composition was significantly affected caused by the two factors.